A Territorial Approach to Climate Action and Resilience (OECD Regional Development Studies, 2023)
Global warming is likely to reach 1.5°C as early as in 2030, with current climate action falling short of meeting the Paris Agreement goals and a mounting risk of tipping beyond the ability of human societies to adapt. Building on broader OECD work on climate, this report proposes a new OECD territorial climate indicator framework and demonstrates that the potential to mitigate greenhouse gas emissions, adapt to climate impacts and address vulnerabilities varies across different territories. The report also presents a policy framework of 9 recommended actions to help decision makers unleash more effective climate action and resilience, both by integrating a territorial approach into national and subnational climate policies and by mainstreaming climate objectives into urban, rural and regional policies. The report summarises the analysis into a checklist for national and local governments to implement a territorial approach to climate and resilience policies, as well as a compendium of 36 best practices from cities, regions and countries from all around the world